DETERMINATION OF ACTIVITY CONCENTRATION OF RADIOACTIVE ELEMENTS IN BOREHOLE AND WELL WATER SAMPLES FROM ADANKOLO NEW LAYOUT LOKOJA (FUDMA JOURNAL OF SCIENCES, 2022)
This study was conducted to determine and compare the activity concentration of natural radioactivity of 238U, 232Th, and 40K in borehole and well water samples collected from Lokoja Nigeria, using Sodium Iodide−Thallium gamma spectroscopy. Samples from selected wells and borehole were collected using standard radiation protocol and analyzed. The result shows that the natural radioactivity concentration of the borehole water sample was 2.77±0.67 Bq/l; 2.30±0.27 Bq/l and 1.66±0.13 Bq/l for 238U, 232Th, and 40K respectively, and 17.62±1.37 Bq/l for 40K in well water while its 238U and 232Th are Below Detection Limit. The results obtained for well and borehole water samples were lower in terms of health risk compared to the World Health Organization (WHO) values (i.e., 10B q/l, 1Bq/l and 4.40 Bq/l for 238U, 232Th and 40K respectively) except the 40K in well water which was higher. The absorbed dose rate for the well water sample was found to be 0.49±62 nGy.hr−1 and 0.09±1.17 nGy.hr−1 for the borehole water. The radium equivalent activity for the well water sample was also calculated to be 1.36±62 Bq/l and 6.19±1.17 Bq/l for the borehole water sample. The evaluated annual effective dose for the well water sample was 0. 00060mSv.y−1 and 0.000096±1.17 mSv.y−1for borehole water sample. The results of the estimated radiological parameters in this study are lower than the International Commission on Radiological Protection (ICRP) maximum permitted limit. Hence, most of them have no significant radiological effect on the environment and its populace except the 40K in the well water sample which
Keywords: specific activity, efficiency, equivalent activity, radiological parameters